Management of poppy (Papaver somniferum L.) stand height using growth regulators - Tomáš Spitzer; Jan Bílovský (Plant Protection Science, 2017)
The possibility of reduce the length of poppy plants and their risk of lodging by applying selected plant growth regulators and effects on the plant and yield were studied in field experiments during 2010-2012. Statistically significant reduction was achieved only with ethephon (576 g a.i./ha) in all experimental years. In 2010 reduction for metconazole (60 g a.i./ha) was recorded. In 2012, ethephon at rates of 576 and 288 g a.i./ha prevented significantly poppy lodging. The 576 g a.i./ha rate was phytotoxic and decreased yield. The commonly used 576 g a.i./ha rate diminished heights by 16-20 cm in all experimental years and significantly reduced lodging in 2012, but decreased yields in two of the 3 years.